Surgery for Patients With cT3/4N2M0, Stage IIIB NSCLC. Is It Time to Redefine Resectability? - J. Humberto Rodriguez-Quintero, MD, MPH; Rajika Jindani, MD, MPH, MS; Roger Zhu, MD; Isaac Loh; Mohamed K. Kamel, MD; Anne Montal, MD; Marc Vimolratana, MD, MS; Neel P. Chudgar, MD; Nitin Ohri, MD, MS; Balazs Halmos, MD, MS; Brendon M. Stiles, MD (JTO Clinical and Research Reports)
Introduction: Chemoradiation followed by durvalumab is considered a standard approach for patients with locally advanced NSCLC. With improvements in perioperative and neoadjuvant approaches, there is renewed interest in offering surgery to carefully selected patients with cT3/4N2 stage IIIB cancer. We sought to assess survival outcomes after surgery as part of a multimodality treatment regimen for these patients. Methods: Patients with cT3/T4N2M0 NSCLC who received surgery (S) as part of a multimodality approach and patients receiving multimodality treatment without surgery (chemoradiation [CRT] or systemic therapy only) were identified in the National Cancer Database (2010–2019). We evaluated factors associated with the receipt of S (logistic regression). After propensity matching, we estimated the overall survival (OS) of patients who received S and compared with those who received CRT (Kaplan-Meier and Cox regression). Results: A total of 44,756 patients were identified, of whom 3928 (8.8%) underwent S, 29,798 (66.6%) CRT, and 11,030 (24.6%) systemic therapy only. Fewer comorbidities (Charlson-Deyo index 0 or 1, adjusted OR [aOR]: 1.22, 95% confidence interval [CI]: 1.05–1.42), treatment at an academic facility (aOR: 1.70, 95% CI: 1.52–1.89), private insurance (aOR: 2.44, 95% CI: 1.61–3.69), adenocarcinoma histology (aOR: 1.48, 95% CI: 1.22–1.79), and clinical T3 stage (<7 cm, aOR: 1.70, 95% CI: 1.53–1.89) were associated with S. In well-balanced, propensity-matched cohorts, patients selected for S had better OS compared with those who underwent CRT (hazard ratio 0.59, 95% CI: 0.56–0.63, p < 0.001) (median OS 49.7 versus 25.0 mo). Conclusions: In this retrospective cohort analysis, patients with cT3/4N2, stage IIIB NSCLC who underwent surgical resection had better OS compared with those patients treated with CRT. Careful patient selection is undoubtedly critical, but stage IIIB designation alone should not exclude patients from surgical consideration.